Estudo in silico de diterpenos abietanos contra o fotoenvelhecimento - Moura, Jéssica Paiva de (2023)
Photoaging is the premature aging of the skin caused by chronic exposure to ultraviolet radiation. Currently, the intervention used to prevent photoaging refers to the use of sunscreen, but studies report that it is difficult for the population to apply the ideal amount for adequate protection. Therefore, continuous research into new strategies is essential to prevent undesirable effects caused by sun exposure. In silico analyzes are important approaches used in the process of discovering drugs against photoaging. They allow the analysis of the physicochemical properties and biological activities of compounds, and reduce the financial costs and time of the process of discovering new drugs. Natural products are secondary metabolites of plants that offer potential for the development of new medicines. Therefore, the objective of this study was to perform in silico analyzes and develop a virtual screening of natural products against photoaging targets. In this work, 1630 natural products were selected to begin virtual screening. The methodologies used in this work were: the construction of QSAR (Quantitative Structure-Activity Relationship) models, the analysis of cytotoxicity risks, the analysis of violations of Lipinski's rule of five, the consensus principal component analysis (CPCA), principal component analysis (PCA) and molecular docking. The result of the QSAR study exhibited adequate statistical parameters and provided molecules likely to be active against photoaging targets, including matrix metalloproteinase-1 (MMP-1) and matrix metalloproteinase-12 (MMP-12). These molecules were evaluated in relation to the risks of cytotoxicity and the number of violations of Lipinski's rule of five. Among those that did not present risks and did not demonstrate violations, the abietane diterpenes with probable multi-target activity were selected, obtaining: JS781, JS887, JS1233, JS1241, JS1352 and JS1513. The interaction of these abietan diterpenes with CYP2D6 resulted in metabolites that did not demonstrate risks of cytotoxicity, with the exception of metabolites M3, M6 and M8. CPCA and PCA indicated that abiethane diterpenes have hydrophobic regions, hydrophilic regions, hydrogen bond donor groups and hydrogen bond acceptor groups. Furthermore, JS1352 showed a better solubility profile compared to the other studied abiethane diterpenes. In molecular docking, the abiethane diterpenes and controls performed similar interactions with some amino acid residues of MMP-1 and MMP-12, through hydrogen bonds or hydrophobic interactions. Given these results, it is believed that the six abiethane diterpenes analyzed possibly have activity against these targets and could be useful in the search for compounds against photoaging.